THE IMPLEMENTATION OF CLINICAL SUPERVISION TO IMPROVE THE ABILITY OF TEACHERS IN MANAGING LEARNING PROCESS AT SDN MENANGGAL 601 SURABAYA - Mohammad Samsul Hadi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
Supervision carried out through the PTS is group supervision, while the approach used is a collaborative approach. The purpose of this supervision is to improve the competence of lower grade teachers in planning thematic learning. Thus this study is entitled "THE IMPLEMENTATION OF CLINICAL SUPERVISION TO IMPROVE THE ABILITY OF TEACHERS IN MANAGING LEARNING PROCESS AT SDN MENANGGAL 601 SURABAYA." Based on facts and field observations as the principal, the teachers seemed to understand the performance evaluation and Academic Supervision carried out by supervisors towards them. However in reality, there are still many teachers who do not understand the evaluation and supervision after both activities were conducted